1997
DOI: 10.1111/j.2042-7158.1997.tb06134.x
|View full text |Cite
|
Sign up to set email alerts
|

Garlic Compounds Protect Vascular Endothelial Cells from Oxidized Low Density Lipoprotein-induced Injury

Abstract: Oxidation of low density lipoprotein (LDL) has been recognized as playing an important role in the initiation and progression of atherosclerosis. In this study, the effects of aged garlic extract and one of its major compounds, S-allylcysteine, on oxidized LDL-induced cell injury were studied. Pulmonary artery endothelial cells were pre-incubated with the garlic extract (1, 2.5 and 5 mg mL-1) or S-allylcysteine (0.1, 1, 10 and 20 mM) at 37 degrees C and 5% CO2 for 24 h, washed, and then exposed to 0.1 mg mL-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(64 citation statements)
references
References 12 publications
1
63
0
Order By: Relevance
“…Food processing can enhance antioxidant potential by inhibition of enzymatic activity and transformation of antioxidants into more active compounds. It may also reduce antioxidant potential because of loss of certain aspects of their bioactivities when kept at high temperatures (Pedraza-Chaverri et al 2006) or cooked (Ide and Lau 1997). Knowledge about the effective loss of total antioxidant activity consequent to home processing may have a significant impact on consumers' food selection and processing.…”
Section: Introductionmentioning
confidence: 99%
“…Food processing can enhance antioxidant potential by inhibition of enzymatic activity and transformation of antioxidants into more active compounds. It may also reduce antioxidant potential because of loss of certain aspects of their bioactivities when kept at high temperatures (Pedraza-Chaverri et al 2006) or cooked (Ide and Lau 1997). Knowledge about the effective loss of total antioxidant activity consequent to home processing may have a significant impact on consumers' food selection and processing.…”
Section: Introductionmentioning
confidence: 99%
“…Zahid et al announce that garlic extract is a vasorelaxant and may decrease the atherogenic potentials of cholesterol concentration in rats [29]. Aged garlic extract (AGE) has been acquaint to prevent lipid oxidation and oxidative modification of low density lipoprotein (LDL), just like that decreasing the amount of oxidized low density lipoprotein (LDL) in circulation and the subsequent build-up of cholesterol in macrophages, smooth muscles and blood vessel walls, leading to the suppression of atherogenic fatty streaks [30]. Both human and animal studies, the water and lipid soluble ingredient in garlic demoralize cholesterol synthesis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Mei [24] noted the absence of nitrites in the gastric juice of people who ate regularly garlic as part of their food. In a series of studies Lau and associates [26][27][28] demonstrated that several garlic compounds can minimize oxidation of LDL cholesterol in vitro. Short term supplementation of garlic in human subjects has demonstrated an increased resistance of LDL to oxidation [29].…”
Section: Antioxidant Actions Of Allium Productsmentioning
confidence: 99%